Pembuatan dan Karakterisasi Keramik Magnet BaFe12O19 dengan Variasi Waktu Milling dan Temperatur Sintering - Syaiful Izzuddin Salam; Edi Sanjaya; Muljadi Muljadi (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2019)
In this study, we made ceramic magnet of barium hexaferrite (BaFe12O19) with variation of milling time and sintering temperature by powder metallurgy method. First, barium hexaferrite powder mashed with a rotary ball mill. Milling is done with medium of water (wet milling) for 4 hours and 12 hours. Then, the sample is dried for 24 hours and printed with a load of 8 tons for 1 minute. Then, the pellet-shaped sample sintered at a temperature of 1100 °C and 1200 °C with a holding time of 1 hour. The density and porosity measurements were carried out using the Archimedes Method, phase analysis with XRD, and magnetic flux density using gaussmeter. The highest density were found in samples that were milled for 12 hours and sintered at the temperature of 1200 °C ie 4.495 gr/cm3. In that sample also obtained the lowest porosity  0.89%. From XRD analysis, we knew that hematite (Fe2O3) was found as impurity phase. From gaussmeter, the samples with the highest magnetic flux density were found in samples that were milled for 4 hours and sintered at a temperature of 1200 °C ie 410.3 G.